Impact of task characteristics on employee agility: the moderating effect of enterprise social media visibility. Issue 3 (30th March 2021) - Zhu, Mengyi; Sun, Yuan; Jeyaraj, Anand; Hao, Jie
Abstract : Purpose: This study aims to explore whether and how task characteristics affect employee agility in the context of enterprise social media (ESM). Design/methodology/approach: Adopting the social network ties perspective, this study examines how task characteristics (i.e. task complexity, task interdependence and task non-routineness) affect employee agility by promoting their social network ties (i.e. instrumental ties and expressive ties) and how ESM visibility moderates their relationships. Data gathered from 341 ESM users in workplaces were analyzed using Smart-PLS 3.2. Findings: First, task complexity, task interdependence and task non-routineness have positive effects on instrumental and expressive ties, which in turn influences agility; Second, instrumental ties have a stronger effect on employee agility relative to expressive ties; Finally, ESM visibility positively moderates the effects of task complexity and task non-routineness on social network ties. Practical implications: The findings provide guidance for organizational managers on how to use task characteristics and ESM to improve employee agility, as well as insights for social media designers to optimize ESM functions to improve agility. Originality/value: This study provides empirical evidence to explain the roles of task characteristics and social network ties in influencing employee agility, thus clarifying the inconsistent findings in extant research. The moderating effects of ESM visibility on the relationships between task characteristics and social network ties are also examined, thus providing further insights on the positive role of ESM in organizations.